Prediction and Design of Efficient Exciplex Emitters for High‐Efficiency, Thermally Activated Delayed‐Fluorescence Organic Light‐Emitting Diodes. (25th February 2015) - Liu, Xiao‐Ke; Chen, Zhan; Zheng, Cai‐Jun; Liu, Chuan‐Lin; Lee, Chun‐Sing; Li, Fan; Ou, Xue‐Mei; Zhang, Xiao‐Hong
<x xml:space="preserve">Abstract</x> High‐efficiency, thermally activated delayed‐fluorescence organic light‐emitting diodes based on exciplex emitters are demonstrated. The best device, based on a TAPC:DPTPCz emitter, shows a high external quantum efficiency of 15.4%. Strategies for predicting and designing efficient exciplex emitters are also provided. This approach allow prediction and design of efficient exciplex emitters for achieving high‐efficiency organic light‐emitting diodes, for future use in displays and lighting applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>